Mughal-Era Social Conditions in India and Their Evaluation (Integral Research, 2025)
The social, economic, and literary landscape of Mughal India was multidimensional and dynamic. With the establishment of Muslim rule, a new process of cultural interaction and synthesis began within Indian society. As a result, society appeared to be broadly divided into three main classes: upper, middle, and lower. The upper class included nobles, feudal lords, and high-ranking officials, who led lives of considerable luxury. The middle class consisted of merchants, state employees, and skilled artists. The lower class comprised peasants, laborers, and artisans, whose conditions were generally difficult and economically constrained. The status of women varied according to class, religion, and prevailing social customs. Practices such as purdah, child marriage, sati, and dowry were prevalent in many sections of society. At the same time, some upper-class women actively participated in education and literary pursuits. Economically, the Mughal system was primarily agrarian; however, industry, crafts, and both internal and overseas trade were highly developed. The textile industry in particular flourished, and major Indian ports facilitated extensive maritime commerce. Significant progress was also achieved in literature and the arts during this period. From Babur to Shah Jahan, most Mughal rulers extended patronage to scholars and writers in various languages, especially Persian and Hindi. The composition of historical chronicles, translation projects, and the growth of Bhakti literature enriched the cultural fabric of the age. Thus, the Mughal period stands out as an important phase in Indian history, marked by an integrated pattern of social structure, economic development, and literary advancement.
Keywords: Mughal Period, Social Structure, Economic System, Literary Advancement, Bhakti Movement